Associations of modifiable factors with risk of irritable bowel syndrome - Chen, Ying; Yang, Hong; Song, Jie; Chen, Weiwei; Liu, Ke; Liu, Bin; Luo, Peiyang; Sun, Xiaohui; He, Zhixing; Mao, Yingying; Ye, Ding (Frontiers in Nutrition, 2024)
Background Modifiable factors were found to be associated with the risk of irritable bowel syndrome (IBS) in observational studies, but whether these associations are causal is uncertain. We conducted a Mendelian randomization (MR) study to systematically explore the causal associations of modifiable factors with IBS. Methods Summary-level statistical data for IBS was obtained from a genome-wide association study (GWAS) meta-analysis of UK Biobank (40,548 cases and 293,220 controls) and the international collaborative Bellygenes initiative (12,852 cases and 139,981 controls). Genetic instruments associated with the exposures at the genome-wide significance (p < 5 × 10−8) level were selected from previous GWASs. Mendelian randomization was performed using inverse-variance weighted (IVW) method, supplemented with several sensitivity analyses to evaluate potentially causal relationships between identified contributing factors and IBS. Furthermore, we applied another database from FinnGen (8,116 IBS cases and 276,683 controls) to testify the reliability of the significant associations. Results Seven convincing modifiable factors were significantly associated with IBS after correction for multiple testing. Genetically predicted smoking initiation (OR = 1.12, 95% CI = 1.06–1.18, p = 1.03 × 10−4), alcohol consumption (OR = 0.47, 95% CI = 0.34–0.64, p = 3.49 × 10−6), sedentary behavior (OR = 1.17, 95% CI = 1.07–1.28, p = 4.02 × 10−4), chronotype (OR = 0.92, 95% CI = 0.88–0.96, p = 4.42 × 10−4), insomnia (OR = 1.19, 95% CI = 1.15–1.24, p = 7.59 × 10−19), education (OR = 0.80, 95% CI = 0.74–0.88, p = 5.34 × 10−7), and visceral adiposity (OR = 1.15, 95% CI = 1.06–1.24, p = 7.96 × 10−4). We additionally identified several suggestive factors, including serum magnesium, serum phosphorus, physical activity, lifetime smoking, intelligence, lean body mass, and body mass index (BMI). After pooling the effect estimates from FinnGen, the associations remained significant except for chronotype. Conclusion This MR analysis verified several modifiable risk factors for IBS, thus prevention strategies for IBS should be considered from multiple perspectives on these risk factors.